Effect of an Educational Intervention on Knowledge and Perception Regarding Rational Medicine Use and Self-medication - Jha, Nisha; Ravi, Shankar Pathiyil; Anurag, Marasini (Journal of Nepal Health Research Council, 2018)
Background: Rational use of medicines is important for safe and cost-effective pharmacotherapy. However, nearly half of the medicines available in the market may be used irrationally. The present study assessed the perceptions and knowledge about rational medicine use and responsible self -medication among participants before and after an educational intervention at KIST Medical College, Lalitpur.Methods: An educational module was conducted among healthcare professionals, media personnel and female community health volunteers. The questionnaire was administered before and immediately after the module. The areas addressed were rational medicine use, ethical prescribing, rational drug use situation in Nepal, pharmaceutical promotion, rational self-medication, safe use of antibiotics, and drug use problems in Nepal.Results:  Among healthcare professionals, the rational drug use situation in Nepal and the total score significantly increased post-intervention (p